When Women Terrorise: The Psychopathic La Femme Fatale in East of Eden by John Steinbeck - Mohan, Zahraa Abdullah; Bahar, Ida Baizura; Ujum, Diana Abu; Amin, Hasyimah Mohd (Academy Publication, 2024)
This study focuses on the issue of female psychopathy and the portrayal of an emotionally and mentally disturbed female character in East of Eden (1952) by the contemporary American author, John Steinbeck. Although female characters are like male characters regarding their psychological complexity, the issues of antisocial personality disorders and psychopathy have only been examined in previous studies concerning male characters. Hence, this study focuses on the issue of psychopathy as an antisocial personality disorder explored through the leading female character based on the Psychopathy Checklist-Revised (PCL-R) by the American psychiatrist, Robert Hare (1991). A prominent view on the mentally disturbed female characters is that they are not analysed with equal attention as male characters; thus, this presumption that women are disqualified from psychological conductions on account of their gender is a predicament by itself. Accordingly, this study examines the non-traditional la femme fatale personified through the female character, Cathy Trask, and investigates the author’s portrayal of a female character with antisocial personality disorder tendencies. The findings show that, from a young age, Cathy reveals her lethal inclinations, harnessing her beauty and intelligence not only to her advantage but also to exploit those around her. Cathy also embodies the two “Personality Traits” and “Antisocial” factors and experiences many short-term marital relationships based on Hare’s (PCL-R).